Public Management: A New Public Service Oriented Concept of Public Service - Benson, Linh; Thanh, Huay Thúy; Thao, Bảo Nga (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
This article discusses the application of the new public service concept in serving the public. This is based on the Public Administration Problem in its development which has gone through several stages. As one of the countries in the world, of course, it is part of the global administration system, which always develops in accordance with the development of contradictions and mutual relations between nations in the world. So that the implementation of the new public service can have an impact on the implementation of the New Public Service with an awareness of the real role of the state. It is no longer authoritarian or still chooses who has the right to receive services from the State. In the current context, the practice of Public Administration has led to the principles of the New Public Service paradigm.